2023
DOI: 10.3390/math11030641
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for Approximating Solutions of Split Variational Inclusion and Fixed-Point Problems

Abstract: In this paper, the split fixed point and variational inclusion problem is considered. With the help of fixed point technique, Tseng-type splitting method and self-adaptive rule, an iterative algorithm is proposed for solving this split problem in which the involved operators S and T are demicontractive operators and g is plain monotone. Strong convergence theorem is proved under some mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…For other related developments on this topic, we refer the readers to Maingé [19], who obtained common fixed-point convergence results by extending Mȃruşter's convergence theorem (Theorem 1) from one demicontractive mapping to a finite family of demicontractive mappings in a Hilbert space; Adamu and Adam [30]; Arfat et al [31], where the authors investigate a fixed-point problem involving an infinite family of k-demicontractive operators in conjunction with the split common null point problems (SCNPP) in Hilbert spaces by using an accelerated variant of the hybrid shrinking projection algorithm; Maingé and Mȃruşter [32]; Anh et al [33]; Charoensawan and Suparatulatorn [34]; Lin [35]; Mongkolkeha et al [36]; Wang et al [37]; Xiao et al [38]; Zhu and Yao [39], etc.…”
Section: The Fixed-point Problemmentioning
confidence: 99%
“…For other related developments on this topic, we refer the readers to Maingé [19], who obtained common fixed-point convergence results by extending Mȃruşter's convergence theorem (Theorem 1) from one demicontractive mapping to a finite family of demicontractive mappings in a Hilbert space; Adamu and Adam [30]; Arfat et al [31], where the authors investigate a fixed-point problem involving an infinite family of k-demicontractive operators in conjunction with the split common null point problems (SCNPP) in Hilbert spaces by using an accelerated variant of the hybrid shrinking projection algorithm; Maingé and Mȃruşter [32]; Anh et al [33]; Charoensawan and Suparatulatorn [34]; Lin [35]; Mongkolkeha et al [36]; Wang et al [37]; Xiao et al [38]; Zhu and Yao [39], etc.…”
Section: The Fixed-point Problemmentioning
confidence: 99%
“…In the above-mentioned work and related literature, we found that the step size, which is under the control of norm ∥A * A∥, is required for the convergence of iterative schemes. To overcome this regulation, a new form of iterative schemes have been proposed, see, e.g., [16][17][18][19]. L ópez et al [20] proposed a relaxed iterative scheme for (S p FP):…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Akutsah et al [28] introduced a new algorithm for finding a common fixed point of generalized nonexpansive mappings. Moreover, the fixed point problems have been studied in many aspects, see for instance [29][30][31][32][33]. Inspired by Bot et al [16], Artsawang and Ungchittrakool [25] introduced the inertial Mann-type algorithm for finding a fixed point of a nonexpansive mapping and applying to monotone inclusion and image restoration problems as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Assume that Fix(S) ∩ Fix(T) = ∅ and by employing (33), then the following algorithm can be constructed for solving (35) as follows:…”
mentioning
confidence: 99%